Treatment Of Pulp And Paper Mill Wastewater Using Moringa Oleifera Via Coagulation-Flocculation Treatment Process - Chum, Chinson (2020)
High levels of total suspended solids (TSS) and chemical oxygen demand (COD), as well as the presence of fibre in difficult-to-manage effluent from the pulp and paper (P&P) industries, remains a common concern due to its negative effects on the environment, especially on the surrounding waterbodies. Coagulation-flocculation is an important process in most wastewater treatment plants to remove a significant amount of suspended solids from the wastewater. At present, prolong exposure to residual amounts of common coagulants such as alum was found to be problematic as it can lead to several problems such as Alzheimer’s disease or a huge volume of non-biodegradable sludge. Therefore, the objective of this project is to study the potential of a plant-based coagulant known as Moringa oleifera seed powder for the treatment of P&P wastewater. Alum is used as a benchmark coagulant for this study along with M. oleifera seed powder. Treatment efficiency was compared in terms of TSS and COD removal. The one-factor-at-a-time approach (OFAT) was used to screen the factors which affect the coagulation efficiency in this preliminary study. Each factor was investigated by adjusting its parameter trough jar tests: dosage (0, 0.5, 1.0, 1.5, 2.0, 2.5 g/L), pH (3, 5, 6.5, 8, 10), stirring speed (20, 40, 60, 80, 100 rpm) and settling time (0, 5, 10, 15, 20, 25 min). Dosage of 1.0 g/L, pH 6.5, stirring speed of 40 rpm and settling time of 20 min were determined as the optimum condition for treatment of P&P wastewater based on the OFAT approach. M. oleifera was able to achieve 85.59 and 29.62% whilst alum achieved 90.62 and 35.09% for TSS and COD removals respectively at optimum condition. The morphology, functional groups, crystallinity and thermal stability of coagulants were characterised using SEM-EDX, FTIR, XRD and TGA, respectively.